Objective Evaluation Of On-Eye Optical Quality Of Daily Disposable Silicone Hydrogel Contact Lens With Internal Wetting Agents - Koh S (Dove Medical Press, 2019)
Shizuka Koh,1,2 Kiyoshi Watanabe,3 Kohji Nishida2 1Department of Innovative Visual Science, Osaka University Graduate School of Medicine, Osaka, Japan; 2Department of Ophthalmology, Osaka University Graduate School of Medicine, Osaka, Japan; 3Watanabe Eye Clinic, Osaka, JapanCorrespondence: Shizuka KohDepartment Of Innovative Visual Science, Osaka University Graduate School Of Medicine, Room E7, 2-2 Yamadaoka, Osaka 565-0871, JapanTel +81-6-6879-3456Fax +81-6-6879-3458Email skoh@ophthal.med.osaka-u.ac.jpPurpose: To investigate the on-eye optical quality of a daily disposable silicone hydrogel contact lens with internal wetting agent.Patients and methods: Study subjects were daily disposable soft contact lens wearers (N=20) who were instructed to wear daily disposable hydrogel etafilcon A lens (without added wetting agent) or daily disposable silicone hydrogel senofilcon A lens (with an internal wetting agent), for a week. Subjects wore their respective lenses bilaterally and disposed of the pair of lenses daily. At the end of the 1-week test-wear period, the on-eye visual performances of the lens and the ocular surfaces were evaluated. A wavefront sensor measured sequential ocular higher-order aberrations (HOAs) for 10 s after the blink. The aberration data were analyzed in the central 4-mm diameter up to the sixth-order Zernike polynomials. Total HOAs, fluctuation index (FI), and stability index (SI) of the total HOAs over time were compared between the two lenses. Ocular surface evaluation with fluorescein was performed following the wavefront measurement.Results: The senofilcon A lens had significantly lower average total HOAs, FI, and SI (p<0.001, p=0.001, p=0.007, respectively) than the etafilcon A lens. After 1-week wear of each lens, corneal staining was observed in eight subjects (40%) with the etafilcon A lens and in two subjects (10%) with the senofilcon A lens. The senofilcon A lens had significantly lower incidence of corneal staining than the etafilcon A lens (p=0.041).Conclusion: Quantitative sequential measurement of HOAs objectively showed the possibility of better and more stable optical quality with silicone hydrogel daily disposable contact lens with the internal wetting agent than with hydrogel lens without the added wetting agent.Keywords: visual performance, quantitative assessment, surface lens wettability